TEACHERS’ PERSPECTIVES ON THE USE OF INTERACTIVE EDUCATIONAL AVATARS: INSIGHTS FROM NON-FORMAL TRAINING CONTEXTS - Danimir Mandić; Gordana Miscević; Miroslava Ristić (Istraživanja u Pedagogiji)
The present study explores how experiences gained through non-formal education influence teachers' attitudes toward the use of interactive educational avatars in pedagogical practice. Employing a quantitative design, data were collected from a sample of 34 educators in Serbia across diverse educational levels (preschool, primary, secondary, and higher education). Data were obtained via an online survey and analyzed using regression analysis, one-way ANOVA, Tukey HSD test, correlation models, and interaction regression models, with support of R statistical software. The findings reveal that respondents generally recognize the educational potential of interactive avatars, particularly in the domains of personalized learning, adaptation to learners' interests and cognitive styles, and fostering intrinsic motivation. University professors displayed the most favorable attitudes, while secondary school teachers showed slightly lower scores. Statistically significant group differences emerged, demonstrating that higher educational attainment corresponds to more favorable perceptions of avatar integration. Participants emphasized the need for additional training to effectively apply avatars in teaching. The study concludes that, with proper teacher training and the development of pedagogically grounded scenarios, interactive avatars can significantly contribute to the digital transformation of education and enhance the learning process through personalized and emotionally intelligent instruction.